2015
DOI: 10.1177/1527154415584233
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Nurse Practitioner Standards for Practice Australia

Abstract: This article describes the context and development of the new Nurse Practitioner Standards for Practice in Australia, which went into effect in January 2014. The researchers used a mixed-methods design to engage a broad range of stakeholders who brought both political and practice knowledge to the development of the new standards. Methods included interviews, focus groups, surveys, and work-based observation of nurse practitioner practice. Stakeholders varied in terms of their need for detail in the standards.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…In Australia, for example, expanded practice is not synonymous with either advanced nursing practice or advanced practice nursing, but may refer to specific situations in which experienced nurses are authorised to practice beyond the RN scope of practice in a specific context (Stasa, Cashin, Buckley, & Donoghue, 2014). In that country, definitional clarity was an essential prerequisite before nurse practitioner (NP) practice standards could operate effectively (Cashin et al, 2015).…”
Section: Conceptual Confusion and Role Claritymentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, for example, expanded practice is not synonymous with either advanced nursing practice or advanced practice nursing, but may refer to specific situations in which experienced nurses are authorised to practice beyond the RN scope of practice in a specific context (Stasa, Cashin, Buckley, & Donoghue, 2014). In that country, definitional clarity was an essential prerequisite before nurse practitioner (NP) practice standards could operate effectively (Cashin et al, 2015).…”
Section: Conceptual Confusion and Role Claritymentioning
confidence: 99%
“…Conceptualised as involving key activities related to research, education, practice, system support and leadership (Cashin et al, 2015), the clinical nurse consultant (CNC) role is analogous to the advanced practice role and the practice nursing role. However, the CNC role has been dogged by conceptual confusion due to lack of clarity over role function (Giles, Parker, & Mitchell, 2014).…”
Section: Conceptual Confusion and Role Claritymentioning
confidence: 99%
“…() reported on the elements that either supported or restricted the NP's scope of practice: the regulatory environment as reflected in the requirement to have physician supervision in nurse prescribing, and physician collaboration and support, whereas Cashin et al. () referred to nurse practitioners as educators meaning role models and mentors to nurses and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Cashin et al. () found that nurse practitioners in Australia, rather than moving further in the same direction of specialisation, become more generalist.…”
Section: Discussionmentioning
confidence: 99%
“…The access of the NP MBS item numbers in the NT is extremely low compared to the other States/Territories and it is likely that very few NPs are working there in private practice (Australian Government, Department of Human Services, ). A recent study identified the percentage of all NPs per State/Territory in Australia as follows: NSW (26%), Queensland (25.5%), Western Australia (17.7%), Victoria (12.9%), South Australia (9.2%), Australia Capital Territory (3.9%), and NT (1.3%; Cashin et al., ). While the number of PPNPs in Australia remains unknown, with reference to Table , the participants in this study are similarly representative of NPs in each State/Territory of Australia, except the NT.…”
Section: Discussionmentioning
confidence: 99%